2017
DOI: 10.3389/fpubh.2017.00314
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cigarette Smoking during Pregnancy on Endocrine Pancreatic Function and Fetal Growth: A Pilot Study

Abstract: IntroductionCigarette smoking in pregnancy is a common cause of fetal growth restriction. We aimed to investigate endocrine pancreatic function of mother–infant dyads in relation to cigarette smoking, as a possible mechanism for the poor fetal growth.MethodsProspective study of smoking mothers (10 cigarettes or more per day, self-reported to the midwife) and non-smoker control mothers during their first pregnancy. Insulin, glucose, C-peptide, HbA1C, fructosamine, prolactin, serotonin, and cortisol were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…In our analysis, we found that maternal smoking increased the risk for IUGR only for female offspring (OR=1.93, 95%CI: 1.14-3.28), suggesting a manifestation of gender differences on the effects of cigarette smoking. In fact, Lockhart et al observed a significant increase of serotonin in smoking mothers carrying male fetuses compared with smoking mothers carrying female fetuses (35). However, factors associated with the intrauterine environment, which lead to these differences, require further research.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, we found that maternal smoking increased the risk for IUGR only for female offspring (OR=1.93, 95%CI: 1.14-3.28), suggesting a manifestation of gender differences on the effects of cigarette smoking. In fact, Lockhart et al observed a significant increase of serotonin in smoking mothers carrying male fetuses compared with smoking mothers carrying female fetuses (35). However, factors associated with the intrauterine environment, which lead to these differences, require further research.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that fetal exposure to tobacco smoke in utero may lead to changes in the secretion of adiponectin isoforms and insulin-dependent growth factors, which may consequently lead to a reduction in the birth weight of the child. Maternal smoking during pregnancy is a well-known cause of low birth weight in infants and has been associated with an increased risk of adiposity, insulin resistance, and type 2 diabetes in children and adults [ 14 , 18 ]. There are several mechanisms that may explain the pathophysiological relations between smoking and adiponectin downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…The first report on the increased risk of fetal hypotrophy in smoking women was published in 1957, and to this day, studies are being carried out with the aim of explaining the changes in the mother as well as the child provoked by tobacco smoke [ 9 ]. Newborns of smoking mothers weigh an average of 88–450 g less at birth than newborns of non-smoking mothers, and the underweight grows proportionally to the number of cigarettes smoked [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. According to Grjibovski et al [ 17 ] and Lockhart et al [ 14 ], birth weight decreased 27–41 g per cigarette smoked per day during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Lockhart F et al, observed that low mean birth weight was associated with maternal cigarette smoking. 9 Zheng W et al, demonstrated that maternal age has a modifying effect on the association between maternal smoking and birth weight. 10 Suzuki K et al, concluded from their study that the child growth was affected in proportion to the degree of maternal smoking.…”
Section: Discussionmentioning
confidence: 99%